2011
DOI: 10.1182/blood-2010-11-319053
|View full text |Cite
|
Sign up to set email alerts
|

KNG1 Ile581Thr and susceptibility to venous thrombosis

Abstract: Three single nucleotide polymorphisms (SNPs) were recently found to be associated with activated partial thromboplastin time (aPTT). Because shortened aPTT levels have been observed in patients experiencing venous thrombosis (VT), we investigated the effects of these 3 aPTT-associated SNPs, rs2731672, rs9898, and rs710446, on the risk of VT in a sample of 1110 healthy patients and 1542 patients with VT. Among the 3 tested SNPs, only rs710446 was associated with VT risk; the rs710446-C allele was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 19 publications
1
51
0
2
Order By: Relevance
“…Thus, the biological interpretation of the results may be done separately. The univariate GWAS confirmed that SNP rs9898 is associated with Histidine Rich Glycoprotein (HRG) levels, but previous results also reported that it was associated with Activated Prothrombin Time (aPTT) trait and consequently with thrombosis risk [8, 31]. This explains why, as observed in Fig 1.c, the metaphenotype obtained with PCA is oriented clearly to the HRG trait.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, the biological interpretation of the results may be done separately. The univariate GWAS confirmed that SNP rs9898 is associated with Histidine Rich Glycoprotein (HRG) levels, but previous results also reported that it was associated with Activated Prothrombin Time (aPTT) trait and consequently with thrombosis risk [8, 31]. This explains why, as observed in Fig 1.c, the metaphenotype obtained with PCA is oriented clearly to the HRG trait.…”
Section: Discussionsupporting
confidence: 58%
“…35,36 In this regard, it is important to point out that SNP rs710446 has also recently been found to be associated with increased risk of venous thrombosis in 2 independent samples from Marseille (odds ratio=1.20 [1.07-1.34]). 37 Our findings, taken together with other observations in KNG1 knockout mice, 38 suggest that genetic variation in KNG1 may be important in determining both the function of the intrinsic pathway of coagulation and the risk of thrombosis. Furthermore, the mechanistic pathway by which KNG1 affects aPTT and risk of thrombosis may be to a large extent through regulation of FXI concentration, which has in fact been proposed as a risk factor for deep vein thrombosis too.…”
Section: Discussionmentioning
confidence: 88%
“…27 In addition to studies in animals, global genetic linkage analysis of mutations in humans has identified a common HK variant located in domain 6 that is linked to greater susceptibility to deep vein thrombosis and changes in coagulation. 35 This missense mutation Ile563Thr is located directly N-terminal to the HK ISDFP sequence (highlighted in Figure 3A as a star). Directly C-terminal to the HK ISDFP sequence is the Cys596 residue, which is implicated in forming a disulfide bond with Cys10 from the HK N-terminus, although the complete disulfide bonding has been reported previously only for splice variant low-molecular-weight kininogen, 36 and not for HK.…”
Section: Discussionmentioning
confidence: 99%